Toward inclusive food systems: Pandemics, vulnerable groups, and the role of social protection - Kumar, Neha; Quisumbing, Agnes R.; Gelli, Aulo; Gentilini, Ugo; Shapleigh, Sara (International Food Policy Research Institute, 2021)
Vulnerable groups have been most affected by disruption to food systems, such as lockdowns, through loss of employment and incomes. Social protection has a key role to play in times of health and economic shocks. KEY MESSAGES - Poverty, poor health, and malnutrition not only result from pandemic stresses, but they also contribute to pandemic-related risks that impact wellbeing and worsen existing inequities. - Vulnerable groups have been most affected by disruptions to food systems, such as lockdowns, through loss of employment and incomes. - The urban poor, especially informal workers and women, have likely borne the brunt of health and employment impacts. Refugees and internally displaced persons have also been disproportionately affected. - Men, women, and children experience different risks and stresses. Women have been more likely to experience increased domestic violence and food insecurity, reduced autonomy, and loss of income. - Social protection is critical for supporting vulnerable groups, and has expanded to an unprecedented degree. But many people were still left without coverage, and programs were rarely gender sensitive.